2017
DOI: 10.2500/ajra.2017.31.4387
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Surgery of a Sinonasal Inverted Papilloma: Surgical Strategy, Follow-up, and Recurrence Rate

Abstract: Endoscopic surgery may be preferred for treating SNIP. The elevated recurrence rate after revision emphasized the significance of the first surgery. We encourage a follow-up period of at least 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…Furthermore, it has been shown that the specific resection technique correlates with recurrence rates. Attachment-oriented resection leads to decreased recurrence rates (<10%) [2,12,16,17,18,21,69,70]. This technique involves subperiosteal tumor resection at the site of tumor origin with a safety margin of 1–1.5 cm [12,15,16,18,38,69].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that the specific resection technique correlates with recurrence rates. Attachment-oriented resection leads to decreased recurrence rates (<10%) [2,12,16,17,18,21,69,70]. This technique involves subperiosteal tumor resection at the site of tumor origin with a safety margin of 1–1.5 cm [12,15,16,18,38,69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the risk of recurrence of SNIP is likely to be a consequence of incomplete surgical resection, rather than due to specific characteristics of the tumor itself, particularly because most SNIP recur at the same site where the tumor originated . Thus, the concept of SNIP resection has changed from aggressive surgery to pedicle‐oriented endoscopic surgery . However, some studies have recommended routine endoscopic surgery combined with an advanced endonasal approach or external approach, because some sites of the tumor origin were located in anatomic areas, which were hard to access by endoscopy alone …”
Section: Discussionmentioning
confidence: 99%
“…5,10 Thus, the concept of SNIP resection has changed from aggressive surgery to pedicle-oriented endoscopic surgery. 2,5,6,22 However, some studies have recommended routine endoscopic surgery combined with an advanced endonasal approach or external approach, because some sites of the tumor origin were located in anatomic areas, which were hard to access by endoscopy alone. 23,24 In this study, we performed a retrospective cluster analysis of data from a preliminarily investigation involving a cohort of 200 patients with SNIPs from 6 centers and developed a staging system for assessment of SNIP recurrence risk and appropriate surgical approach recommended, based on the originating site of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…While we aimed to acquire long-term data on IP recurrence within our cohort, with a mean follow-up of 31.1 months, this still may not have adequately captured all cases of recurrence. It has been reported that up to 20% of recurrences may occur 5 years after resection for all IPs [ 28 ]. However, specific for maxillary IPs, recurrences have been noted to occur within a mean time of 20 months [ 7 ].…”
Section: Discusssionmentioning
confidence: 99%